Assessment of levator hiatal area using 3D/4D transperineal ultrasound in women with deep infiltrating endometriosis and superficial dyspareunia treated with pelvic floor muscle physiotherapy: randomized controlled trial. (3rd May 2021) - Del Forno, S.; Arena, A.; Pellizzone, V.; Lenzi, J.; Raimondo, D.; Cocchi, L.; Paradisi, R.; Youssef, A.; Casadio, P.; Seracchioli, R.
ABSTRACT: Objectives: Deep infiltrating endometriosis (DIE) is associated with chronic pelvic pain, dyspareunia and pelvic floor muscle hypertonia. The primary aim of this study was to evaluate the effect of pelvic floor physiotherapy (PFP) on the area of levator ani hiatus during Valsalva maneuver, assessed using transperineal ultrasound, in women with DIE suffering from superficial dyspareunia. Methods: This was a randomized controlled trial of 34 nulliparous women diagnosed with DIE and associated superficial dyspareunia. After an initial clinical examination, all patients underwent three‐dimensional/four‐dimensional (3D/4D) transperineal ultrasound to measure the levator hiatal area (LHA) at rest, on maximum pelvic floor muscle contraction and on maximum Valsalva maneuver, and were asked to rate their pain symptoms using a numerical rating scale (NRS). Eligible women were assigned randomly (1:1 ratio) to no intervention (control group, 17 women) or treatment with five individual sessions of PFP (study group, 17 women). Four months after the first examination, all women underwent a second evaluation of pain symptoms and LHA on transperineal ultrasound. The primary outcome measure was the percentage change in LHA on maximum Valsalva maneuver between the baseline and follow‐up examinations. The percentage changes in pain symptoms between the two examinations, including superficial and deep dyspareunia, dysmenorrhea, chronic pelvic pain, dysuria and dyschezia, were also evaluated. Results: Thirty women, comprising 17 in the study group and 13 in the control group, completed the study and were included in the analysis. The percentage change in LHA on maximum Valsalva maneuver between the two examinations was higher in the study group than in the control group (20.0 ± 24.8% vs –0.5 ± 3.3%; P = 0.02), indicating better pelvic floor muscle relaxation. After PFP treatment, the NRS score for superficial dyspareunia remained almost unchanged in the control group (median change in NRS (Δ‐NRS), 0 (interquartile range (IQR), 0–0)) while a marked reduction was observed in the study group (median Δ‐NRS, –3 (IQR, –4 to –2); P < 0.01). Moreover, there was a significant difference between the PFP and control groups with regards to the change in chronic pelvic pain (median Δ‐NRS, 0 (IQR, –2 to 0) vs 0 (IQR, 0–1); P = 0.01). Conclusions: In women with DIE, PFP seems to result in increased LHA on Valsalva maneuver, as observed by 3D/4D transperineal ultrasound, leading to improved superficial dyspareunia, chronic pelvic pain and pelvic floor muscle relaxation. © 2020 International Society of Ultrasound in Obstetrics and Gynecology Abstract : Linked article: There is a comment on this article by Hirsch et al. Click here to view the Correspondence.